STUDI PERANCANGAN KAPAL PENANGKAP IKAN 5 GT ELEKTRIK DENGAN TENAGA SURYA SEBAGAI SUMBER ENERGI UTAMA - Ulul Azmi Aziz (2021)
In the midst of the increasing number of capture fisheries production, fishermen complain about the difficulty of getting fuel, Meanwhile on the other hand Indonesia as a country located on the equator gets sunlight all year round, it will be an advantage to use solar energy as a source of energy on fishing vessels. From the calculation results, electric fishing boats equipped with solar panels can produce 14.3% of their energy needs independently and have lower operating costs but with a much higher initial investment cost.